Surgical management of tuberculum sellae meningioma: Transcranial approach or endoscopic endonasal approach? - Qian, Kang; Nie, Chuansheng; Zhu, Wende; Zhao, Hongyang; Zhang, Fangcheng; Wang, Haijun; Jiang, Xiaobing (Frontiers in Surgery, 2022)
Background: Tuberculum sellae meningioma (TSM), a common benign tumor in the sellae region, usually causes neurological deficits, such as vision impairment, by squeezing the peripheral neurovascular structures. Surgical management is recommended as the optimal strategy for TSM treatment and vision restoration. However, it remains challenges to resect TSM in traditional transcranial approach (TCA). Recently, endoscopic endonasal approach (EEA) has emerged as an effective option in skull base surgeries. Besides the effectivity, the advantages and limitations of EEA in TSM surgery remain controversial. Object: We compared the surgical outcomes and complications between TCA and EEA surgeries to identify the principles in TSM surgical management. Methods: Retrospective analysis was performed on the patients, who underwent TSM surgery in Wuhan Union Hospital between January 2017 and December 2021. The patients were assigned to TCA or EEA group according to the surgery they experienced. All patients were analyzed with the extent of tumor resection, vision outcome, postoperative complications and follow-up results. Results: A total of 112 patients were enrolled in this study, including 78 in TCA group and 34 in EEA group. The mean follow-up was 20.5 months (range 3-36months). There were no statistically significant differences in patient demographic data, preoperative symptoms and tumor characteristics between TCA and EEA groups. Both TCA and EEA surgeries are effective in TSM resection with relatively high gross total resection (GTR) rates (85.9% in TCA vs. 91.2% in EEA, p＞0.05). Meanwhile, EEA surgery has a better outcome in vision restoration or stabilization than TCA surgery (74.6% in TCA vs. 93.1% in EEA, p＜0.05). Whereas, EEA surgery causes more occurrences of cerebrospinal fluid (CSF) leakage than TCA surgery (0% in TCA vs. 11.8% in EEA, p＜0.05). Conclusion: Both TCA and EEA surgeries are effective in TSM resection. EEA surgery has a better outcome in vision restoration or stabilization than TCA surgery, but induces higher risk of CSF leakage. As each approach has unique advantages and limitations, we must take all aspects into consideration, including approach feathers, tumor characteristics and clinical requirements, to make the optimal choice in TSM surgical management.